Studi Analisis Kesulitan Belajar Matematika dan Upaya Menanganinya pada Siswa Kelas V SD Muhammadiyah 6 Surakarta Tahun Ajaran 2016/2017 - Perwira, Widya; *, Dra. Ratnasari Diah Utami, M.Si., M.Pd (2017)
This research aims to describe: 1) The material which was considered difficult by grade V who have difficulty in studying at odd Semester Mathematics in Muhammadiyah 6 Elementary School of Surakarta. 2) Characteristics of mathematical learning difficulties experienced by students of grade V in SD Muhammadiyah 6 Surakarta, 3) Factors of Mathematical learning difficulties experienced by grade V in Muhammadiyah 6 Elementary School of Surakarta, 4) Teachers in dealing with mathematical learning difficulties experienced by students of grade V in Muhammadiyah 6 Elementary School of Surakarta. This type of research is qualitative research. Informants in this study is grade V students who have difficulty in learning Mathematics, grade V, teacher grade IV, teacher grade III, teachers and parents of students. Data collection techniques used are observation, interview, and documentation. Data were analyzed through data reduction steps, the presentation of data, and the withdrawal of the conclusion. Techniques of examination of the validity of the data is done by triangulation of sources and techniques. The results showed that: 1) The material of Mathematics that considered difficultt by students who have difficulty in learning Mathematics is multiplication, distribution, multiples and factors, exponentiation and square root, time, distance, speed, the area trapezoid and kite, 2) Characteristics of the disorders are visual perception disorders (including memory, sequence, and abstraction) and the difficulties in language and reading, 3) Factors that affect students, among others, the interest and motivation of learning Mathematics are low, families who have not optimally support, and lack of learning Mathematics media used by the teacher. 4) Efforts made by teachers among others providing tutoring in groups on additional hours, asking the students who are good at to help Mathematics other students who are having difficulty in learning Mathematics, carring out tests remidial, and giving additional tasks to do at home. Keywords: Characteristic, Learning Difficulties, Mathematic.